Group portrait of eleven people - London Irish Centre, LIC
Black and white group portrait photograph of a eleven people, including Fr Jerry Kivlehan (standing, at left), John McDonnell MP (standing, in centre) and Mo Mowlam MP (seated, at right). The other five men and three women are unidentified. The bottom of a banner with the words 'North London branch' and a sign saying '25 years congratulations' can be seen behind them. A handwritten note on the back reads 'North London CCE 25th anniversary'. Photographer unknown.